Observations on the alewife, Pomolobus pseudoharengus (Wilson), in fresh water - Graham, Joseph J. (University of Toronto biological series ;, 1956)
The major study in this investigation was one of growth and form, carried out to evaluate differences in growth rates and body proportions between landlocked Lake Ontario and the anadromous Atlantic alewives. Particular attention was also given to the nature of the annual mortality that is characteristic of P. pseudoharengus in Lake Ontario.